Pengaruh Pelatihan dan Pengembangan Karir Terhadap Kinerja Pegawai pada Dinas Pengendalian Penduduk dan Keluarga Berencana (DPPKB) Karawang - Abizachryan Akbar; Sari Marliani; July Yuliawati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This research was conducted at the Population and Family Planning Control Service of Karawang, The purpose of the research is to analyze training and career development on employee performance and to test the influence between variables. The method used is quantitative descriptive and verification with a census approach (total sampling), involving all employees as a sample of 37 respondents. Data were obtained through observation, interviews, and questionnaires with a Likert scale. The analysis used Multiple Linear Regression and used SPSS version 26, The results showed that training with an average value of 125.4 which is in the range of 96.3-126 scale with a fairly good category, career development with an average value of 127.1 which is in the range of 126-156.6 scale with a good category and employee performance with an average value of 126.2 which is in the range of 126-156.6 scale with a good category. Partially, training has a positive and significant effect on employee performance with a Sig value of 0.000 <0.05 and a calculated t of 5.090> t table 2.206, Career development partially has a positive and significant effect on employee performance with a Sig value of 0.001 <0.05 and a calculated t of 3.736> t table 2.206, Simultaneously, both variables have a positive and significant effect on the dependent variable of employee performance with a Sig value of 0.001<0.05 and a calculated f of 269.391> from f table 3.28, The coefficient of determination obtained an R Square value of 94.1% in employee performance can be explained by variations in training and career development, while the value of 6.9% is influenced by other factors not examined in this study.